Steel, C. Ed. (2012). Aristotle's Metaphysics Alpha: Symposium Aristotelicum. Oxford, Oxford University Press. - Laks, André (Revista Archai, 2015)
Steel, C. ED. (2012). Aristotle's Metaphysics Alpha: Symposium Aristotelicum. Oxford, Oxford University Press.